Modeling and simulation of anaerobic manure digestion into biogas - Danielsson, Oskar (My University, 2014)
Today it becomes more and more expensive to take care of produced manure, not only from horses, but also from zoos. This project, that is a small part of a large collaboration, aims to develop methods to test co digestion of manure and waste water sludge to biogas. In the project a model based on the Anaerobic Digestion Model No. 1 (ADM1) is built. To this standard model further equations have been added and simulations have been build, with the aim to develop tools to investigate the possibilities to co digest manure and sludge. Interesting aspects such as optimal mixture and parameter dependence are investigated. The work is performed in MATLAB, but to make wider use of the project result, a stand alone graphical user interface is also created. This lets peoples without knowledge about or access to MATLAB use the build model.
Keywords: Energi; Grundläggande vetenskaper; Hållbar utveckling; Innovation och entreprenörskap (nyttiggörande); Annan teknik; Energy; Basic Sciences; Sustainable Development; Innovation & Entrepreneurship; Other Engineering and Technologies